Cross-Platform Sentiment Analytics for Unified Customer Feedback in Digital Business Environments - Samuel Augustine Umezurike,; Onyinye Gift Ejike,; Bisayo Oluwatosin Otokiti,; Omolola Temitope Kufile,; Oluwatolani Vivian Akinrinoye,; Abiodun Yusuf Onifade, (International Journal of Scientific Research in Science and Technology, 2025)
This paper explores cross-platform sentiment analytics to unify customer feedback in digital business environments, enabling organizations to gain actionable insights from diverse data sources such as social media, reviews, and surveys. A systematic literature review synthesizes insights on sentiment analysis techniques, cross-platform data integration, and their applications in customer experience management. A proposed framework integrates these elements into a cohesive system for real-time feedback analysis. Application scenarios in retail, hospitality, and financial services illustrate the framework’s potential, suggesting up to 30% improvement in customer satisfaction and 25% increase in retention rates. The study contributes to the literature on digital business intelligence and offers practical guidelines for leveraging sentiment analytics to enhance customer-centric strategies.
Keywords: cross-platform analytics; sentiment analysis; customer feedback; digital business; data fusion; NLP; domain adaptation